PENGARUH BIG FIVE PERSONALITY TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KASUS DI PT. RUMPUN SARI MEDINI KENDAL) - Sartika, Indah Ayu; Rahayu, Sri; Nurmiyati, Nurmiyati (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2024)
Job satisfaction is a positive feeling shown by each individual in a job, which is the impact or result of evaluating various aspects of the job. With various levels of job satisfaction, which can be assessed from the level of personality of each employee through personality. The purpose of this writing is to find out and analyze the relationship between variables, namely Openness to experience (X1), Conscientiousness (X2), Extraversion (X3), Agreeableness (X4), Neuroticism (X5), and Job satisfaction (Y). This type of research is quantitative research. The population in this study was 144 with a sample of 106 people. The results of the analysis show that Openness to experience has an effect on job satisfaction with acquisition (t count 3.335> t table 1.660), Conscientiousness on job satisfaction has an effect on acquisition (t count 4.130 > t table 1.660), Neuroticism on job satisfaction has an effect on acquisition (t count 2.375 > t table 1.660). While the Extraversion variable on job satisfaction has no effect on gain (t count 0.376 <t table 1.660), Agreeableness on job satisfaction has no effect on gain (t count 1.218 <t table 1.660). Simultaneous test results Openness to experience, Conscientiousness, Extraversion, Agreeableness, Neuroticism on job satisfaction together have an influence on job satisfaction with the results of calculating the value (Fcount 33.824 > Ftable 2.31) with a significance level (0.000 <0.05) . From the results of the coefficient of determination simultaneously Openness to experience, Conscientiousness, Extraversion, Agreeableness, Neuroticism on job satisfaction explains 61%.Keywords: Openness to experience, Conscientiousness, Extraversion, Agreeableness, Neuroticism and job satisfaction.